2020
DOI: 10.3389/fphar.2020.00092
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone Modulates α2A-Adrenergic, TRPV1, and NMDA NR2B Receptors Plasticity in CCI-Induced Neuropathic Pain In Vivo and LPS-Induced SH-SY5Y Neuroblastoma In Vitro Models

Abstract: the anti-allodynic and anti-hyperalgesic effects of zerumbone. b 1 -adrenoceptor antagonist only reversed the anti-allodynic effect of zerumbone. The anti-allodynic and anti-hyperalgesic effects of zerumbone were both absent when TRPV1 and NMDA receptors were antagonized in both nociceptive assays. Zerumbone treatment markedly decreased the expression of a 2Aadrenoceptor, while an up-regulation was observed of NMDA NR2B receptors. Expression of TRPV1 receptors however did not significantly change. The in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 103 publications
(121 reference statements)
0
17
0
Order By: Relevance
“…Changes in paw volume were measured as previously described [31]. noxious stimulus produced by formalin injection, the rats were lightly anesthetized and 50 µL of 5% formalin solution was injected subcutaneously (s.c.) into the dorsal surface of the right hind paw with a 30-g needle.…”
Section: Paw Edema Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in paw volume were measured as previously described [31]. noxious stimulus produced by formalin injection, the rats were lightly anesthetized and 50 µL of 5% formalin solution was injected subcutaneously (s.c.) into the dorsal surface of the right hind paw with a 30-g needle.…”
Section: Paw Edema Measurementmentioning
confidence: 99%
“…MPO activity, an index of polymorphonuclear cell accumulation, was determined as previously described in the hind paw tissues of all experimental groups [31]. The rate of change in absorbance was measured spectrophotometrically at 650 nm.…”
Section: Myeloperoxidase Activity (Mpo Activity)mentioning
confidence: 99%
See 1 more Smart Citation
“…The NO-cGMP pathway activation and K + channels have been shown to correlate [ 92 , 93 ]. In a recent report by the research team, the antiallodynic and antihyperalgesic effects of zerumbone were shown to interact with the noradrenergic system, TRPV1, and NMDA receptors [ 94 ]. The noradrenergic system has been shown to act synergistically with the opioidergic pathway at both spinal and supraspinal sites [ 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Liang et al (2017) revealed that the intrathecal administration of dexmedetomidine attenuated mechanical allodynia and thermal hyperalgesia in the CCI model of the sciatic nerve in Sprague-Dawley rats (11). Similarly, Chia et al (2020) revealed that the administration of zerumbone (the main bioactive compound, a wild ginger plant species) have anti-allodynia and anti-hyperalgesia effects via activation of α-and β-adrenoceptors in the CCI-induced neuropathic pain mouse model (12). Therefore, it is suggested that α-adrenoceptors have an important role in the processing of pain information in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%